1992
DOI: 10.1007/bf02252998
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, outcome, and proposed management of isolated abscesses complicating acute left-sided colonic diverticulitis

Abstract: In a prospective evaluation of 140 consecutive patients with acute left-sided colonic diverticulitis demonstrated by computerized tomography (CT) in all cases, 22 (16 percent) were found to have an associated abscess without peritonitis. Thirteen of these 22 required surgery (seven during the first stay and six from 2 to 11 months after the acute episode; median, three months). Nine patients were treated conservatively, eight of whom are now totally asymptomatic 24 months after the initial attack (range, 10-47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 8 publications
0
39
0
1
Order By: Relevance
“…However, Ambrosetti et al 6,16 observed that both intraabdominal and pelvic abscesses were associated with a significant risk of surgery compared with a mesocolic abscess. The latter had a lower risk of requiring surgery once adequately drained.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ambrosetti et al 6,16 observed that both intraabdominal and pelvic abscesses were associated with a significant risk of surgery compared with a mesocolic abscess. The latter had a lower risk of requiring surgery once adequately drained.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our previous and recent experience with 31 patients we think that the evolution of these abscesses is more related to their localization than to their size (mean size of mesocolic abscesses was 4.1 vs. 5.4 cm for pelvic abscesses) [34], Abdominal and pelvic abscesses have a more aggressive behavior since the 3 abdominal abscesses and 11 of the 13 pelvic abscesses required surgical treat ment. Therefore, for abdominal and pelvic abscesses we would recommend percutaneous drainage followed 4-6 weeks later by one-stage colectomy if possible.…”
Section: Discussionmentioning
confidence: 99%
“…Small pericolic abscesses (Stage I) can often be treated conservatively with antibiotics and bowel rest (68). Their favorable prognosis may be attributed to a persistent fistula between the abscess and the colon, permitting spontaneous internal drainage.…”
Section: Complications Of Diverticulitismentioning
confidence: 99%